Assessment of Masticatory Function Using Bite Force Measurements in Patients Treated for Mandibular Fractures. Issue 4 (December 2013) - Sybil, Deborah; Gopalkrishnan, K.
Bite force measurements are excellent criteria for assessment of masticatory efficiency. The purpose of this study was to assess the effect of mandibular fractures on the bite forces of patients treated for such fractures. Patients who were surgically treated for isolated mandibular fractures in the Department of Oral and Maxillofacial Surgery from January 2006 to December 2007 were included in the study. Patients were asked to bite on a bite force transducer on the first, fourth, sixth, and ninth postoperative weeks. The bite force values were compared with those of age, sex, and weight-matched controls. A total of 60 patients were included in the study. It was found that maximum bite forces in patients were significantly less than in controls for several weeks after surgery. After the ninth postoperative week, the maximum bite force measured < 65% the normal in patients with isolated angle fractures and > 80% the normal in patients with isolated parasymphysis fractures. The same values reduced to < 60% in patients with fractures of angle and parasymphysis and < 70% in patients with fractures of parasymphysis and condylar complex. An inverse relationship was found between the bite force values and the number of fractures of the mandible. We also found lower bite forces and longer period for normalization in patients who had fractures in those regions of the mandible which are more significantly associated with the masticatory apparatus for example angle or condyle of the mandible.